Wettability characteristics of laser surface textured plasma sprayed TiO2/ZnO coatings - Ghazali, Mariyam Jameelah; Yusuf, Yusliza; Abdollah, Mohd Fadzli bin; Otsuka, Yuichi; Morakul, Sarita; Nakamura, Susumu; Ohnuma, Kiyoshi (Japanese Society of Tribologists, 2019)
Surface wettability behaviour is generally categorised as hydrophobic and hydrophilic depending on the contact angle value. Surface wettability has been attracting considerable attention in research due to its unique behaviour in the field of self-cleaning, anti-fouling and anti-corrosion. Surfaces with high and low wettabilities can be fabricated using various methods, including chemical etching, anodisation and laser surface texturing. The present study investigated the effects of textured surfaces via laser surface texturing on the wettability properties of TiO2/ZnO coatings. TiO2/ZnO coating was selected due to its high photocatalytic activity, non-toxicity and low cost, which are essential properties for self-cleaning and anti-fouling applications. Picosecond laser ablation was used to produce microdimple textures on the coating surfaces. The wettability of the laser-textured surfaces was greatly reduced, achieving superhydrophilic properties with contact angle of 1.4° ± 2.42° for laser-textured TiO2 coating. On the other hand, coatings with ZnO compositions exhibited increased contact angles for both textured and non-textured surfaces. Moreover, no clear cut correlations between the surface roughness properties of non-textured and laser-textured TiO2/ZnO coatings and the surface wettability properties was observed. This finding provides new approaches in designing textured surface materials that can effectively increase the wettability properties for selfcleaning and anti-fouling applications